2010
DOI: 10.1103/physrevb.81.085211
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure of acceptor-bound excitons in wide-band-gap wurtzite semiconductors

Abstract: We describe the internal structure of acceptor-bound excitons in wurtzite semiconductors. Our approach consists in first constructing, in the context of angular momentum algebra, the wave functions of the two-hole system that fulfill Pauli's exclusion's principle. Second, we construct the acceptor-bound exciton states by adding the electron states in a similar manner that two-hole states are constructed. We discuss the optical selection rules for the acceptor-bound exciton recombination. Finally, we compare ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…In recent years the development of solid state light emitters for the blue to ultraviolet (UV) spectral range has caught rising interest which naturally results in the task of bipolar doping of intermediate and wide bandgap materials like CdS, [1][2][3] ZnSe, 4 ZnO 5-7 and GaN. 1,8 Up to date only GaN and its ternary systems InGaN and AlGaN have matured towards technologically relevant applications as e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years the development of solid state light emitters for the blue to ultraviolet (UV) spectral range has caught rising interest which naturally results in the task of bipolar doping of intermediate and wide bandgap materials like CdS, [1][2][3] ZnSe, 4 ZnO 5-7 and GaN. 1,8 Up to date only GaN and its ternary systems InGaN and AlGaN have matured towards technologically relevant applications as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1,8 Up to date only GaN and its ternary systems InGaN and AlGaN have matured towards technologically relevant applications as e.g. blue and near UV light-emitting diodes 9,10 and blue laser diodes as originally invented by Nakamura et al 11,12 While sufficient n-type conduction for light emitting devices was achieved in the early years of GaN growth, p-type doping with resulting predominant p-type conduction was an outstandingly challenging task until the breakthrough of Amano et al, 8 and Akasaki et al 13 The first p-conducting GaN samples where doped with Mg and subsequently activated by low energy electron beam irradiation (LEEBI) in order to remove the acceptor passivating hydrogen which originates from the metal organic chemical vapor deposition (MOCVD) growth procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MQDs' structure in which each nanostructure can be assumed as a single QD (the absence of wavefunction overlap among those of different QDs), the main absorption coefficient component is related to QDs' bound excitons [35,43,47,[49][50][51][52]. Instead, in this paper, our investigation is focused on absorption coefficient components derived by thesuperlattice nature of high density QD heterostructures.…”
Section: Exciton Absorptionmentioning
confidence: 99%
“…The doublet line ABE1 is due to Mg contamination in the growth system. It was recently demonstrated that acceptor BEs (ABEs) in wurtzite wide bandgap semiconductors are expected to exhibit several radiative states 7 . Fig.…”
Section: Annealing and Optical Measurementsmentioning
confidence: 99%